PERANCANGAN KEMASAN MAKANAN KUE BAWANG ONION CAKE USAHA MURNI DI KOTA BATUSANGKAR KABUPATEN TANAH DATAR - TEGAR PRAKARSA SYAFRIMA, Hendra Afriwan, S.Sn, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The devolopment of small and medium industries is one of the backbone of national economic development. One of the home industries is “Usaha Murni” onion cake, snack food from Batusangkar, Tanah datar Regency has a delicious and tasty taste. The purpose of designing “Usaha Murni” onion cake packaging is to produce attractive and efficient packaging and brand designs in the hope of attracting the attention of buyers so that they can increase sales. The method used in data collection is by conducting observations, interviews, and documentation. While the method used to analyze the data is a SWOT analysis. To strengthen packaging design various supporting media are designed in the from of mugs,hats, x-banner, business card, t-shirt, posters and key chains.Keywords : Packaging, Onion Cake, Usaha Murni